The evolution of partial undercutting facetectomy in the treatment of lumbar spinal stenosis - Cawley, Derek T. (J Spine Surg, 2018)
Decompression of lumbar spinal stenosis is the most common spinal surgery in those over 60 years of age. While this procedure has shown immediate and durable benefits, improvements in outcome have not changed significantly. Technical aspects of surgical decompression have evolved significantly. The recently introduced ultrasonic bone cutter allows a precise and safe peri-neural bone resection. The principles of preservation of stability, as described by Getty et al. have remained as relevant as when these were described 40 years ago.